Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Bank Syariah Mandiri (Studi Kasus Pada Kantor Cabang Pembantu Pulo Brayan Medan) - Munawaroh Munawaroh (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to determine how to quality of of Bank Syariah Mandiri KCP Pulo Brayan Medan and is most dominant variabel in influencing towards customer satisfaction Bank Syariah Mandiri KCP Pulo Brayan Medan. The observation is an assosiative one, that is an observation which looks for the relation between one variable with another variable. During sample taking stage, the researcher uses accidental sampling technique. A total of 92 repondents involved in the study. Data are analyzed using double regression with 0,05 significance level or ???? = 5 %. Based on the result of the study, it is known that service quality variables reliability, responsiveness, assurance, empathy and physical have positive and significant on Bank Syariah Mandiri KCP Pulo Brayan Medan. And the most significant effects of service quality is physical (X5), responsiveness (X2), reliability (X1), assurance(X3) and empathy (X4) towards customer satisfaction. R2= 0,482 shows that 48,2% customer satisfaction variables can be explained by variables in service quality dimension as follows: reliability (X1), responsiveness (X2), Assurance (X3), Empathy (X4), Physical (X5), whereas another 76,7% can be explained by other variables which do not include in the model.